A year full of stories : 366 days of story and rhyme - Adams, Georgie; Young, Selina (London : Orion, 1997)
A collection of stories, poems, holiday tales, humor, fantasies, and retellings of best-loved classics, with one for each day of the year.
3.5
K-3
Keywords: Children's literature, English; English literature -- Collections; Children's literature; English literature -- Collections